Razones para sentir depresión durante la pandemia en población peruana - Sánchez-Villena, Andy Rick (2024)
During the pandemic, the most prevalent psychological disorder worldwide was depression, which increased two to threefold compared to the pre-pandemic situation. However, little is known about the specific reasons that triggered it. Therefore, the aim was to explore the specific reasons why the Peruvian population experienced depression during the COVID-19 pandemic. A total of 3918 people participated, with an average age of 42.66 years (65.9 % women), whose data and responses were extracted from the Demographic and Family Health Survey of Peru 2021 (ENDES-2021). Participants responded to the question “In the last 12 months, when was one of the times you had these complaints or problems when was it”, which referred to the symptoms described by the PHQ-9. The findings indicated that the reasons why the Peruvian population felt depressed were grief due to illness, death and separation from significant persons, health issues, economic and interpersonal problems, stress due to lack of work and, to a lesser extent, academic reasons. Comparisons by gender did not show significant differences; however, there was a greater tendency for women to worry about children and pregnancy, while men worried about economic issues. It is concluded that the reasons why the Peruvian population became depressed during the pandemic were mainly economic-academic, family and health reasons, from which specific reasons are broken down, such as couple problems, bereavement due to the death of significant persons and concern for children.